Theme Session A - Oceanography and ecosystems in the North Atlantic: science and operational services ... - ICES (ASC 2022 - Theme session A, 2024)
ICES Annual Science Conference Book of abstracts of theme session A: Oceanography and ecosystems in the North Atlantic: science and operational services Conveners: Tomasz Dabrowski (Ireland), Caroline Cusack (Ireland), Marcos Llope (Spain) CM 26: Non-linearity in interspecific interactions between Barents Sea cod and haddock in response to climate change CM 48: The role of large spawners for population productivity in Northeast Arctic cod CM 84: Resilience for whom and according to what criteria? An examination of adaptations to changes in the Bay of Biscay anchovy fishery CM 85: Impacts of the match-mismatch hypothesis across three trophic levels – a case study in the North Sea CM 88: Temporal dynamics and climatic forcing of dissolved inorganic nutrient chemistry in the western Irish Sea: evidence from a long-term oceanographic observatory CM 141: Remote sensing for quantitative mapping of kelp (Laminaria hyberborea) CM 142: An ecological approach characterizing factors influencing the yellowtail flounder ...